What do physiotherapists do in managing urinary incontinence in women in primary health care? a scoping review protocol - Giovanna Campos Santos; Amanda Damasceno de Souza; Mara Lisiane de Moraes dos Santos (Frontiers in Global Women's Health, 2025)
Urinary incontinence (UI), defined as the involuntary loss of urine, is highly prevalent among women and has a significant impact on physical, emotional, and social well-being. Although pelvic floor muscle training is widely recognized as a first-line intervention for mild to moderate UI, the role of physiotherapists in managing this condition within Primary Health Care (PHC) remains insufficiently explored. Considering the centrality of PHC in health systems and the predominance of generalist and multiprofessional teams in this setting, mapping conservative, low-complexity physiotherapeutic interventions is essential. This article presents a protocol for a scoping review aimed at identifying, examining, and synthesizing the scientific literature on physiotherapeutic practices for the management of UI in women within PHC. The review will follow the Joanna Briggs Institute (JBI) methodology and the PRISMA-P checklist. Eligible sources include full-text peer-reviewed articles, theses, dissertations, and clinical guidelines, with no publication date restrictions. Abstracts, opinion pieces, unrelated studies, and duplicates will be excluded. Additional strategies such as interlibrary loan services and author contact will be employed to access full texts. This review is expected to identify existing practices, knowledge gaps, and opportunities for strengthening physiotherapy care in PHC, contributing to improved health outcomes and future research directions.